СОРБЕНТ КӨМЕГІМЕН ТЕХНЕЦИЙ-99М ӘСЕРІНЕ ҰШЫРАҒАН ЗЕРТХАНАЛЫҚ ЖАНУАРЛАРДАҒЫ ҚАН КӨРСЕТКІШТЕРІН БАҒАЛАУ - A. Абжалиева; А. Узынтлеуова; А. Еркебаева; У. Тастаганова (Animal Health and Biosafety, 2026)
During the study, hematological and biochemical parameters of blood were determined using sarbent. Number of animals: 46 pcs., including 30 mice not exposed to the effect and 16 rats exposed to technetium. Laboratory animals: at the first stage - white mice. At the second stage - Wistar rats. The following parameters were measured during the experiment: leukocytes (WBC), eosinophils (Eo.), basophils (Bas.), erythrocytes (RBC), platelets (PLT), hemoglobin (HGB), hematocrit (HCT), plateletcrit (PCT), as well as the following erythrocyte parameters: mean corpuscular volume of erythrocytes (MCV), mean corpuscular HGB (MCH), mean corpuscular concentration of HGB (MCHC), etc. Calculated parameters: lymphocytes (LYM) %, monocytes (MON) %, neutrophils (NEU) %, Bas. %, Eo. %, etc. The analysis was performed on an automatic hematology analyzer MS 4/5 (France). Blood for biochemical analysis was also taken before irradiation and on the 2.7th day after it. Blood was collected in test tubes. Number of samples: 16. Study conditions: temperature - 25.4°C, relative humidity - 37%. Total protein, g/l AST, U/l, ALT, U/l, ALP, U/l, Total α-amylase, U/l, Pancreatic lipase, U/l, Urea mmol/l, Creatinine, mol/l, Total bilirubin, μmol/l, Glucose, mol/l, Cholesterol, mol/l. A significant difference in the parameters was noted between the control and experimental groups (p < 0.05).